Detection of Some Immunological Parameters in Psoriatic Iraqi Female Patients - Khazem, Rehab Morad; Ibraheem, Shaima R. (Iraqi Journal of Science, 2020)
Psoriasis is a common, chronic, immune-mediated skin disease with systemic pro-inflammatory activation. This study was designed to estimate the level of two cytokines, Interleukin-36 (IL-36) and Interleukin-10 (IL-10), in psoriasis female patients. The study was accomplished on 50 Iraqi patients with psoriasis who were referred to the consulting clinic at Al-Yarmouk Teaching Hospital during the period from November 2018 to March 2019. These patients were diagnosed under the supervision of dermatologists. For the purpose of comparison, the study included 30 healthy women as a healthy control group. The serum levels of cytokines were measured using the enzyme-linked immunosorbent technique (ELISA).The results of this study showed that the mean age of the female patients was 35.9 Â± 1.85 years, whereas the age of the patients with a severity of higher than 30% ranged 15-25 years. Most of the patients were married, in an average living condition, and non-smokers, and their menstrual cycle was continuous. It was also found that 28% of the psoriatic patients had other chronic diseases. The study showed statistically significant differences (p <0.05) in the mean level of IL-36 between the patients and healthy control group, whereas there was no statistical difference in the mean level of IL-10. In conclusion, the decrease in the level of IL-36 in the patients might be related to the increase in the severity of the disease.